Augmented Reality (AR) Based Disaster Responsive Curriculum Design For Arabic Vocabulary Mastery Post-disasters situation - Arniati; Fitri Ananda; Retno Dumilah; M. Rasyid (International journal of technology and education research, 2026)
Indonesia as a vulnerable country disaster face problematic Serious in preparedness face situation emergency, especially limitations mastery vocabulary much needed situational Arabic​ For coordination with team humanity international post- disaster curriculum existing learning​ Not yet integrate in a way systematic material disaster, technology cutting-edge, and mastery vocabulary functional based phase responsive emergency. Research This aim For designing curriculum responsive disaster based on augmented reality (AR) for mastery situational Arabic vocabulary post - disaster. The type of research used is studies library research with data sources in the form of books, articles journal scientific, and reports research. Data collection techniques using documentation, whereas data analysis was performed through analysis content qualitative with three stage reduction, presentation, and withdrawal conclusion. Research results produce four findings main : first, map integration material disaster to in competence base Arabic vocabulary that classifies vocabulary to in three cluster functional ; second, six principle design AR interface for context post-disaster that prioritizes simplicity, durability environment, and offline accessibility ; third, mapping need vocabulary based phase responsive emergency, transition, recovery initial, and reconstruction ; fourth, scenario model learning cycle four phase that synchronizes AR, mitigation, and production oral vocabulary. Research conclusions This is design curriculum responsive disaster effective AR- based For increase mastery situational Arabic vocabulary post-disaster. Implementation results study done through compilation map curriculum, development AR application with six principle design, drafting module based phase, and training facilitator and trial field in the community vulnerable disaster.